Gulliver's Travels - Prue, Sally (Oxford Oxford University Press, 2014)
In Gulliver's Travels Gulliver sets out on a sea voyage hungry for adventure. He is shipwrecked on an island inhabited by tiny people - but every time Gulliver thinks things can't get any stranger, they always do TreeTops Classics are adapted and abridged versions of classic stories to enrich and extend children's reading experiences
Include Illustrations
Keywords: Readers (Elementary)